2013
DOI: 10.6061/clinics/2013(08)08
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diabetes on mortality and length of hospital stay in patients with renal or perinephric abscess

Abstract: OBJECTIVES:We compared the risk of in-hospital mortality and the length of hospital stay between diabetic and non-diabetic patients hospitalized for renal or perinephric abscess.METHOD:The data analyzed in this study were retrieved from Taiwan's National Health Insurance claims. The risk of in-hospital mortality and the length of hospital stay were compared between 1,715 diabetic patients, hospitalized because of renal or perinephric abscess in Taiwan between 1997 and 2007, and a random sample of 477 non-diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 36 publications
(57 reference statements)
3
14
0
Order By: Relevance
“…1b) despite diabetics having overall longer LOS. This is consistent with other studies [25,[27][28][29]. The present study differs from other works by including only people over 65 years and adjusting for the confounding of disease burden by using the CCI.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…1b) despite diabetics having overall longer LOS. This is consistent with other studies [25,[27][28][29]. The present study differs from other works by including only people over 65 years and adjusting for the confounding of disease burden by using the CCI.…”
Section: Discussionsupporting
confidence: 93%
“…Most of studies that deal with mortality and diabetes are longitudinal studies [20][21][22][23][24]. There only a few studies that explore in-hospital mortality associated with diabetes and these are disease speci c [25][26][27]. Two of the studies show not effect on inpatient mortality [25,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 However, other studies reported that diabetes was significantly associated with a longer length of hospital stay among patients with renal abscess, by 3.38 days (95% CI: 1.59-5.17). 18 Also, EMS calls for less urgent condition among diabetics can't be ruled out. 16 DM programs as advised by AHA (American Heart Association) can help to prevent emergencies and EMS calls for less urgent conditions among diabetics.…”
Section: Discussionmentioning
confidence: 99%
“…The worldwide prevalence of diabetes has been reported to be 2.8% and it may rise to 4.4% by year 2030. 2 In Pakistan, the disease burden has dramatically increased in the last few years. Current rate of diabetes in Pakistan is 11.8%.…”
Section: Introductionmentioning
confidence: 99%